2010
DOI: 10.4269/ajtmh.2010.09-0711
|View full text |Cite
|
Sign up to set email alerts
|

Serologic and Molecular Studies of Leptospira and Leptospirosis among Rats in the Philippines

Abstract: Abstract. Rats are known to be the most important reservoirs and transmission sources of leptospirosis. However, the status of leptospirosis in the Philippines regarding reservoirs and transmission remains unknown. A survey was conducted in Metro Manila and Laguna that analyzed samples obtained from 106 rats. Using the microscopic agglutination test, we found that 92% of rat serum samples were positive for anti-Leptospira antibodies; the most common infecting serovars were Manilae, Hebdomadis, and Losbanos. On… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
89
1
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 85 publications
(99 citation statements)
references
References 41 publications
5
89
1
4
Order By: Relevance
“…Other studies reported a low genetic diversity among locally circulating Leptospira strains within the rat population. [27][28][29][30][31][32] Here, we showed that rats in Mayotte carried four genomospecies (Table 4) and that the genetic diversity among Leptospira strains infecting black rats is unique. Rattus sp.…”
Section: Animals As Reservoirs Of Leptospirosis In Mayottementioning
confidence: 99%
See 1 more Smart Citation
“…Other studies reported a low genetic diversity among locally circulating Leptospira strains within the rat population. [27][28][29][30][31][32] Here, we showed that rats in Mayotte carried four genomospecies (Table 4) and that the genetic diversity among Leptospira strains infecting black rats is unique. Rattus sp.…”
Section: Animals As Reservoirs Of Leptospirosis In Mayottementioning
confidence: 99%
“…Rattus sp. is considered as the preferred reservoir host for L. interrogans and L. borgpetersenii [28][29][30][32][33][34] and to our knowledge L. kirschneri (serovar Bim) has only been isolated from rats in Barbados. 35 Our serological results corroborate serological observations and molecular data on human strains and confirmed that field strains from serogroup Icterohaemorrhagiae are absent on Mayotte.…”
Section: Animals As Reservoirs Of Leptospirosis In Mayottementioning
confidence: 99%
“…These ranged from Bayer Philippines' Rat Attack information dissemination programs and distribution of free Racumin products to various municipal ordinances that offered cash payments for every rat caught dead or alive by local residents (Laude, 2009;Philippine Star, 2010). Rat infestation has long been a serious problem, in a country where millions of rats are born annually (Philippine Star, 2010;Villanueva et al, 2010). One study has discovered at least four Leptospira serovars and serogroups circulating among domestic rats in the Philippines.…”
Section: Philippines (Southeast Asia)mentioning
confidence: 99%
“…Another is rat and other rodent infestation, which is further encouraged by tropical and subtropical climates. Scientific studies have consistently indicated that rats are the most significant carriers and transmitters of leptospirosis globally, although other domestic and wild animals are potential reservoirs of the bacteria (Sarkar et al, 2002;GreenMcKenzie and Shoff, 2010;Villanueva et al, 2010). Several Leptospira serovars and serogroups that circulate among rats have already been identified (McBride et al, 2007).…”
Section: Leptospirosis As a Zoonosismentioning
confidence: 99%
“…[5][6][7] Our study evaluated the interlaboratory reliability of PFGE identification of leptospiral serovars between the CDC and the San Antonio Military Medical Center (SAMMC; Fort Sam Houston, TX) leptospirosis laboratories.…”
Section: Introductionmentioning
confidence: 99%